Balancing the banks: global lessons from the financial crisis - Dewatripont, Mathias; Rochet, Jean-Charles; Tirole, Jean; Keith Tribe (Princeton University Press, 2010)
The financial crisis that began in 2007 in the United States swept the world, producing substantial bank failures and forcing unprecedented state aid for the crippled global financial system. Bringing together three leading financial economists to provide an international perspective, Balancing the Banks draws critical lessons from the causes of the crisis and proposes important regulatory reforms, including sound guidelines for the ways in which distressed banks might be dealt with in the future.